Memahami dan Mendorong Terciptanya Employee Engagement dalam Organisasi - T. Elisabeth Cintya Santosa (Jurnal Manajemen Maranatha, 2012)
Employee engagement is a hot topic nowadays because it is a key driver of organizational productivity. A recent study by the Hay Group found that offices with engaged employees were up to 43% more productive based on comparisons of revenue generated. What is employee engagement and how do you know whenemployees are engaged? An engaged employee is a person who is fully involved in, and enthusiastic about, his or her work. More evidence found that high levels of employee engagement correlates to individual, group and corporate performance inareas such as retention, turnover, productivity, customer service and loyalty.